A market-level pricing model for airlines. (1st January 2001) - Curry, R.E.
Airline Revenue Management has typically focused on an optimisation problem choose inventory control settings to maximise revenues. Airline pricing is more difficult because the actions of competitors must be incorporated into the pricing decision leading to a game theoretic formulation. To support this game theoretic view, this paper develops a market-level pricing model that provides insight as to whether an airline should or should not match the new fare of a competitor to maximise revenue. The model also shows that matching competitors' prices preserves market share. The application of consumer choice models to individual flight departures is also discussed.